Cinématique et impacts d’un événement hydrométéorologique : les inondations du 6-7 octobre 2014, Grabels (France méditerranéenne) - Tony Rey; Stéphanie Defossez; Freddy Vinet; Laurent Boissier (VertigO)
Mediterranean area has often concerned area is often hit by flash foods. Grabels (city in southern France) experienced flash floods from 6-7th October 2014. During this time the river “Mosson” and its tributaries overflowed and combined with the streaming to damage near 500 homes. To evaluate the event and its impacts, we performed an analysis days after the disaster to identify the main flow and consecutive damages. We identified the floodplain, the development of the flood and others characteristics on morphosedimentary and hydrologics changes. We also estimate damages and impacts on urbanized area.